2019
DOI: 10.1515/cti-2018-0030
|View full text |Cite
|
Sign up to set email alerts
|

Putting inquiry-based learning into practice: How teachers changed their beliefs and attitudes through a professional development program

Abstract: Despite the tremendous efforts which have been made over the last few years, inquiry-based learning (IBL) has not become an established practice in science education yet. Even if teachers consider IBL an important and valuable approach, they still refrain from implementing it in their own science classes. Research findings suggest that the teachers’ beliefs and attitudes have a crucial influence on their classroom practice. Only if they are compatible with the approach of IBL, the teachers will be willing to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 34 publications
0
12
0
1
Order By: Relevance
“…Vauderwange et al (2019) opines that the above trend is driven by the fact that the research process is explained to them. The researchoriented teaching relies on inquiry-based learning (IBL) concept that is considered an indispensable component of higher education (Hofer & Lembens, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Vauderwange et al (2019) opines that the above trend is driven by the fact that the research process is explained to them. The researchoriented teaching relies on inquiry-based learning (IBL) concept that is considered an indispensable component of higher education (Hofer & Lembens, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The authors stated that research still lacks analytics and statistics. According to Hofer and Lembens (2019), the researchoriented teaching approach needs reshaping to be more consistent with curricula, standards and final exams. Though found significant and effective, the teachers still use it rarely in their classes (DiBiase & McDonald, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The study was guided by the "strongly simplified model of the relationship between attitude, intentions and practice", proposed by Hofer and Lembens (2019). According to the proponents of the model, knowledge and skills, affective factors, and beliefs interact in complex ways to influence teachers' attitudes, which determine their intentions (plans, resolutions, prospects) and may consequently influence their practice (Hofer & Lembens, 2019). Figure 1.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Adopted from Hofer and Lembens (2019). In the study reported here, attributes related to the three dimensions of Hofer and Lembens (2019)'s the model; knowledge and skills, affective factors and beliefs, in relation to attitudes, intentions and practice, were explored.…”
Section: Figure 1 a Strongly Simplified Model Of The Relationship Between Attitude Intentions And Practicementioning
confidence: 99%
“…Ergänzend untersucht die Didaktik bei Aus-und Fortbildungen, wie Lehrende den Prozess der Erkenntnisgewinnung an Experimenten wahrnehmen und vermitteln. Dabei interessiert die Forscher, wie sich Vor-und Einstellungen verändern, 56) wie Lehrende Erkenntnisgewinnungsprozesse gestalten [57][58][59] oder sie erfassen per Video die Experimentierkompetenz der Lehrkräfte. [60][61] Diese Kompetenz erforschen Bewersdorff, Baur und Emden 62) auch in realen Unterrichtssituationen videobasiert und triangulieren sie mit weiteren Testdaten wie dem fachdidaktischen Wissen (pedagogical content knowledge, PCK) und Hospitationen (Unterrichtsbeobachtungen) (Abbildung 7).…”
Section: Experimente Und Experimentierkompetenzunclassified